Effect of surfactant on the physical properties of ZnO nanorods and the performance of ZnO photoelectrochemical cell - Rahman M.Y.A.; Umar A.A.; Taslim R.; Salleh M.M. (Taylor and Francis Ltd., 2023)
Ammonia; Electrochemical cells; II-VI semiconductors; Morphology; Nanorods; Nanostructures; Open circuit voltage; Optical properties; Oxide minerals; Particle size; Photoelectrochemical cells; Surface active agents; Thin films; Tin oxides; Zinc oxide; Cetyltrimethylammonium bromide; Controlled hydrolysis; Fill factor; Fluorine tin oxides; Growth process; Photovoltaic materials; Photovoltaic parameters; Polyvinyl pyrrolidone; Optical films; ammonia; cetrimide; methenamine; povidone; zinc oxide; zinc oxide nanoparticle; Article; cells; electric potential; field emission scanning electron microscopy; hydrolysis; optics; particle size; photoelectrochemical cell; priority journal; short circuit current; X ray diffraction